Chemicals from heavy oils by ZSM‐5 catalysis in supercritical water: Model compound and reaction engineering. Issue 7 (30th April 2020) - Zaker, Azadeh; Guerra, Patricia; Tompsett, Geoffrey A.; Huang, Xinlei; Bond, Jesse Q.; Timko, Michael T.
Abstract: Dodecane cracking and aromatization over ZSM‐5 was studied in the presence and absence of supercritical water (SCW). A group‐type model was used to determine five best‐fit rate constants to describe yields to aliphatics, aromatics, coke, and gases. SCW accelerated gas formation while suppressing coke formation. CO and CO2 were formed in the presence of SCW, but not in its absence; a new, low‐temperature coke gasification pathway was suggested to account for this observation. Similarly, a low‐temperature alkane reforming pathway was hypothesized to explain the increased relative rate constant for production of gases in the presence of SCW compared with its absence. Additional tests and analysis indicated that these effects could not be ascribed solely to zeolite degradation in the presence of SCW, implying that water directly influences the reaction mechanism. These results provide new insights into the role(s) of water during oil cracking under supercritical conditions.